KEMAMPUAN LITERASI MATEMATIKA SISWA KELAS V DALAM MENYELESAIKAN SOAL MATEMATIKA TIPE HIGHER ORDER THINKING SKILLS (HOTS) - Irfani Salsabilla; Yulia Maftuhah Hidayati (JKPD (Jurnal Kajian Pendidikan Dasar), 2021)
This study aims to determine the mathematical literacy ability of students in grade V of SD Negeri Bratan 2 in solving math problems of Higher Order Thinking Skills (HOTS) types prepared by fifth grade teachers at SD Negeri Bratan 2. This research is a descriptive qualitative study with a type of content analysis research. The subjects of this study consisted of 3 research subjects consisting of 1 female student and 2 male students from class V. The methods used in this study included tests, interviews, and documentation. The test tested consisted of 5 HOTS type mathematical description items. The test results are then analyzed and supported by interviews and documentation with students. The results showed, based on the results of tests and interviews with students in grade V of SD Negeri Bratan 2, the mathematical literacy ability of students in solving problems was different. From the aspect of problem solving, students are able to solve and be able to understand problems. From the aspect of formulating problems and using mathematics, students have not fully used concepts and procedures in formulating problems and solving problems using mathematics. From the aspect of communicating, students have not fully written down the answers coherently and do not write down problem solving.